The elemental and biochemical composition of bryophytes from the maritime Antarctic - Davey, Martin C. (Antarctic Science, 1999)
The elemental and biochemical composition of eight moss species from the maritime Antarctic were determined fornightly (summer) or monthly (winter) from December 1992 to November 1994. Short-duration summer carbohydrate maxima in Calliergon sarmentosum were seen in both years, but no other seasonal patterns were observed. The absence of seasonality in carbon, nitrogen and phosphorus concentrations or their atomic ratios suggest that the mosses were nutrient-sufficient throughout the year, and that nutrient availability was not important in determining moss productivity. Mosses from hydric habitats had lower carbohydrate and higher protein, nitrogen and phosphorus contents than those from drier habitats, possibly as a consequence of higher productivity and continual flushing with nutrients in wet habitats. The results are consistent with the importance of water and the primacy of physical factors in the ecology of Antarctic mosses.